Integrative analysis of transcriptome, proteome, and ubiquitome changes during rose petal abscission - Jiang, Chuyan; Jiang, Tianhua; Deng, Shuning; Yuan, Chaoli; Liang, Yue; Li, Susu; Ma, Chao; Gao, Yuerong (Frontiers in Plant Science, 2022)
Plant organ abscission is regulated by multiple physiological and biochemical processes. However, the transcriptional, translational, and post-translational modifications occurring during organ abscission have not been systematically investigated. In this study, we report transcriptome, proteome, and ubiquitome data for the abscission zone (AZ) of rose petals collected during petal shedding. We quantified 40,506 genes, 6,595 proteins, and 2,720 ubiquitinated proteins in rose petal AZ. Our results showed that during petal abscission, 1,496 genes were upregulated and 2,199 were downregulated; 271 proteins were upregulated and 444 were downregulated; and 139 ubiquitination sites in 100 proteins were upregulated and 55 ubiquitination sites in 48 proteins were downregulated. Extracellular levels of cell component proteins were significantly increased, while levels within protoplasts were significantly decreased. During petal abscission, transcript levels of genes involved in defense response, transport, and metabolism changed significantly. Levels of proteins involved in the starch and sucrose metabolism and phenylpropanoid biosynthesis pathways were significantly altered at both the transcript and protein levels. The transcriptional and translational upregulation of peroxidase (POD), in the phenylpropanoid biosynthesis, pathway may be associated with deposition of lignin, which forms a protective layer during petal abscission. Overall, our data provide a comprehensive assessment of the translational and post-translational changes that occur during rose petal abscission.